2018
DOI: 10.1111/hsc.12534
|View full text |Cite
|
Sign up to set email alerts
|

I just can't please them all and stay sane: Adult child caregivers’ experiences of family dynamics in care-giving for a parent with dementia in Australia

Abstract: Family caregivers of people with dementia who live within the community often experience stress and poor quality of life due to their care-giving role. While there are many factors that affect this, one influential factor is the family context. This study focussed on adult child caregivers. It examined the specific ways that family dynamics contribute to adult child caregivers' distress in the context of caring for a parent with dementia. Semi-structured interviews were conducted with 17 participants who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 37 publications
(64 reference statements)
2
35
0
Order By: Relevance
“…This study suggests that family caregivers' psychological well-being is influenced by their relationships with care receivers, consistent with previous findings (Pinquart & Sörensen, 2011). The results also support theoretical assumptions on the basis of caregiving stress process models, sense of control, and meaningful choice (Dowding, 1992;Leotti et al, 2010;Pearlin et al, 1990), as well as previous studies (Longacre et al, 2014;Tatangelo et al, 2018) showing that family caregivers with perceived choices in caregiving reported better psychological well-being than those without choice.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study suggests that family caregivers' psychological well-being is influenced by their relationships with care receivers, consistent with previous findings (Pinquart & Sörensen, 2011). The results also support theoretical assumptions on the basis of caregiving stress process models, sense of control, and meaningful choice (Dowding, 1992;Leotti et al, 2010;Pearlin et al, 1990), as well as previous studies (Longacre et al, 2014;Tatangelo et al, 2018) showing that family caregivers with perceived choices in caregiving reported better psychological well-being than those without choice.…”
Section: Discussionsupporting
confidence: 90%
“…In some cases, it is assumed that a certain family member has more time or capability for caregiving responsibilities, and so that family member becomes the caregiver. Another study found that some people choose to become family caregivers because they do not trust their siblings' capability in taking care of aging parents (Tatangelo, McCabe, Macleod, & Konis, 2018). Therefore, an individual's perception of caregiving choice is affected by many relevant factors in the caregiving context.…”
Section: Caregiving As Choice In Caregiving Contextmentioning
confidence: 99%
“…Whereas adult children who not reside with their parents can be less inclined to offer them support,17,18 ones whose parents’ spouses have passed away or cannot provide care often take responsibility for caring for their parents. At the same time, adult children who have to share different responsibilities and tasks with siblings in caring for their aging parents are more liable than spouses to experience conflict in the family 19,20…”
Section: Introductionmentioning
confidence: 99%
“…In our study, self‐determination was expressed by caregivers' ability to decide which tasks they would do to help their parents and when to do them. Feeling obligated to assume in caregiving responsibilities can lead to a heavier subjective burden among adult children (Conde‐Sala et al., 2010; Tatangelo, McCabe, Macleod, & Konis, 2018). Therefore, being autonomous in the caregiver role is important and, in our study, adult children often seemed to have internalized the value of caregiving, performing tasks without talking about the need for autonomy.…”
Section: Discussionmentioning
confidence: 99%